Adaptasi Perubahan Iklim (Apik) Terhadap Keberadaan Jentik Nyamuk Demam Berdarah Dengue (Dbd) Di Wilayah Kerja Puskesmas Sidomulyo - Zahra, Ayu; Hayana, Hayana; Renaldi, Reno; Susmaneli, Herlina; Yulianto, Beny (LPPM Universitas Muhammadiyah Sumatera Barat, 2025)
Abstract : Sidomulyo Public Health Center experienced an increase in Dengue Hemorrhagic Fever (DHF) cases from 2023 to 2024, marked by a low Larvae Free Index (LFI) of only 4.3%, far below the 95% standard. This study aims to determine the relationship between Climate Change Adaptation (APIK) and the presence of Aedes mosquito larvae, which causes DHF, in the Sidomulyo Health Center's working area. This is a quantitative research with a cross-sectional design, conducted in RW.10, Tuah Karya Village, in March 2025. The study population consisted of 850 households, with a sample size of 90 households selected using Simple Random Sampling. Data collection tools included questionnaires and observation sheets, and data were analyzed using univariate and bivariate analysis with the Chi Square test. The results showed that factors related to larvae presence with a P-value ≤ α 0.05 were: humidity (P-Value 0.019; OR 3.889), knowledge (P-Value 0.019; OR 3.714), and the